Learn computer coding with a serious game: theoretical framework and course performance. (28th November 2022) - Azmi, Kamal; Laraqui, Abderrahmane; Boussedra, Faouzi
Teaching computer science to non-specialists, forms part of the Moroccan university reform perspective. So, the new purpose of the 'teacher/accompanying person' at UCD University is to accompany the learner to be auto-effective regarding a programming language. The classic modes of teaching and the classic methodologies of research on this topic are outdated. The present article tells our experience in a contextualised way, our methodological repositioning before explaining the steps of a theoretical model which reconfigures the phase of the production to favour an accompaniment stimulating the auto-efficacy of the learner. The training games and simulation environment is a better solution for this circumstance. The scenarisation tasks in this type of game are a major issue for the development of self-efficacy; and that will be the goal of this paper.